2016
DOI: 10.5414/cn108671
|View full text |Cite
|
Sign up to set email alerts
|

Acute kidney injury (AKI) outcome, a predictor of long-term major adverse cardiovascular events (MACE)

Abstract: Complete renal recovery after an episode of AKI in patients with normal baseline kidney function is associated with a lower risk of long-term MACE when compared with those who did not fully recover.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 0 publications
3
15
0
Order By: Relevance
“…But, we found that increasing age, black race, high Charlson score, smoking history, primary diagnosis at admission, comorbid history of hypertension and other previous comorbidities predict future MACE after adjusting potential confounders in CKD patients who survived for at least 30 days after AKI. These findings were similar to those earlier reported to contribute to immediate and longterm mortality, progression of CKD and development of cardiovascular outcomes following AKI [20,21,28] .…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…But, we found that increasing age, black race, high Charlson score, smoking history, primary diagnosis at admission, comorbid history of hypertension and other previous comorbidities predict future MACE after adjusting potential confounders in CKD patients who survived for at least 30 days after AKI. These findings were similar to those earlier reported to contribute to immediate and longterm mortality, progression of CKD and development of cardiovascular outcomes following AKI [20,21,28] .…”
Section: Discussionsupporting
confidence: 80%
“…Many factors may have effect on long-term outcomes in patients who survived after AKI [19,20] . In a recent observational data, we showed that complete renal recovery after an episode of AKI is associated with a lower risk of longterm MACE when compared with those who did not fully recover in patients with normal baseline kidney function [21] . Preexisting CKD seems to be one of the most potent predictors of AKI and mortality [20,22] .…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that dialysis dependence after AKI as well as patients progressing from CKD to ESRD are associated with poor cardiovascular outcomes. In a previous retrospective cohort study, patients with incomplete recovery after AKI, had a higher risk of long-term major adverse cardiovascular events compared to those who recovered [13]. Also, ESRD patients are at an increased risk of coronary events [14].…”
Section: Discussionmentioning
confidence: 99%
“…Our group recently identified increasing age, low baseline estimated glomerular filtration rate (eGFR), African American race, Charlson, comorbidity index score, smoking history, pre-admission history of hypertension, diabetes, CVD, heart failure (HF), peripheral vascular disease, MI and incomplete recovery of renal function as predictors of MACE in AKI [14]. However, little is known about any association between major depression and long-term outcomes of AKI.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding AKI and associated outcomes, a few studies have documented the increased risk of long-term major adverse cardiovascular events (MACE), defined as subsequent admission for acute myocardial infarction (MI), cerebrovascular disease (CVD) or congestive heart failure (CHF) following AKI [12,13,14]. Our group recently identified increasing age, low baseline estimated glomerular filtration rate (eGFR), African American race, Charlson, comorbidity index score, smoking history, pre-admission history of hypertension, diabetes, CVD, heart failure (HF), peripheral vascular disease, MI and incomplete recovery of renal function as predictors of MACE in AKI [14].…”
Section: Introductionmentioning
confidence: 99%